Dust in the wind: the growing use of embalming fluid among youth in Hartford, CT. - Singer, Merrill; Clair, Scott; Schensul, Jean; Huebner, Cristina; Eiserman, Julie; Pino, Raul; Garcia, José (Substance use & misuse, 2005)
This study suggests that use of embalming fluid as a mind-altering drug has been underreported. Based on a social network recruitment strategy, findings from a study in 2000 of 401 outreach worker-recruited polydrug-involved youth (ages 16-24 years) from the inner city of Hartford, CT indicate widespread (over 80% of study participants had used the drug at least once) and regular use of embalming fluid mixed with either marijuana or mint. This paper reports findings on frequency and distribution of use, experience, and consequences of use, access to the drug, and characteristics of embalming fluid users. Given the toxic substances that comprise embalming fluid, and the tendency, affirmed in the present study, of the drug to be associated with violent behavior, there is a need to recognize embalming fluid as a drug of concern among youth.
Keywords: Adolescent; Adult; Cannabis; Connecticut; Embalming; Female; Humans; Male; Mentha; Psychotropic Drugs; Street Drugs; Substance-Related Disorders; United States